Flows: Discourses of recent decades - Zheleznyak, Olga (project baikal, 2025)
Flows as a movement, paths/roads, a part of life and a way of self-development, a form of transformation are one of the cultural stereotypes. The theme of flows as an urgent problem of the profession was raised at the World Congress of Architecture in Barcelona in 1996, where ‘man and time’, nomadism and ‘royal’ urbanism, flow and exchange, ‘ambulant science’, mobility and urbanism, transport flows, etc. were investigated. Today, the problem of flows is still important, becoming a global quality/property of the world. Information flows and the Internet, transport and trade flows, E-commerce and logistics system, intensification of migration and tourist flows are also among the topical discourses.